A Survey on Software defined Networking and different types of controllers - Karhikeyani, R; Karthikeyan, E (International Journal of Computer Sciences and Engineering, 2024)
Distributed Denial of Service (DDOS) attacks represent a tool wielded by hackers, cyber extortionist, and individuals involved in cyber terrorism. These malicious activities result in significant financial losses for the targeted victims. Although a myriad of scientific solutions are available, the frequency and intensity of DDOS attacks continue to escalate. In response to the evolving landscape of security threads, a novel network paradigm has emerged. Software Defined Networking (SDN) has garnered considerable attention from numerous researchers it addresses the specific requirement of modern data centres, drawing inspiration from its capabilities. Our study presents a comprehensive examination of current SDN-based solutions for detection and mitigating DDOS attacks. Building upon our findings, we propose an innovative framework designed for the detection and mitigation of DDOS attacks on a large scale network. The primary contribution of this paper is twofold. Firstly, we furnish an in-depth survey of SDN based DDOS attack detection and mitigation mechanisms. Secondly, we offer a detailed comparison of SDN- based controllers.